2014
DOI: 10.3727/096368914x678337
|View full text |Cite
|
Sign up to set email alerts
|

Mannitol-Enhanced Delivery of Stem Cells and Their Growth Factors across the Blood–Brain Barrier

Abstract: Ischemic brain injury in adults and neonates is a significant clinical problem with limited therapeutic interventions. Currently, clinicians have only tPA available for stroke treatment and hypothermia for cerebral palsy. Owing to the lack of treatment options, there is a need for novel treatments such as stem cell therapy. Various stem cells including cells from embryo, fetus, perinatal, and adult tissues have proved effective in preclinical and small clinical trials. However, a limiting factor in the success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 91 publications
(130 reference statements)
0
57
0
Order By: Relevance
“…However, systemic injection requires overcoming the blood brain barrier (BBB) in order to achieve adequate entry of stem cells into the CNS. Mannitol injection has been extensively used to transiently open the BBB and has also been shown to enhance delivery of stem cells to the brain [11, 25]. In our study, we used this method to open the BBB, followed immediately by injection of 1 × 10 5 hUC-MSCs via the carotid artery.…”
Section: Discussionmentioning
confidence: 99%
“…However, systemic injection requires overcoming the blood brain barrier (BBB) in order to achieve adequate entry of stem cells into the CNS. Mannitol injection has been extensively used to transiently open the BBB and has also been shown to enhance delivery of stem cells to the brain [11, 25]. In our study, we used this method to open the BBB, followed immediately by injection of 1 × 10 5 hUC-MSCs via the carotid artery.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these initially encouraging results from a preliminary clinical study conducted in patients affected from lymphoma and treated with mannitol and cyclophosphamide [121], further studies have shown subsequent ineffective BBB disruption of the circumventricular organs [122] and non-selective disruption of the BBB surrounding tumors [104]. The non-selective nature of this treatment has thus raised concerns regarding its toxicity and efficacy throughout the CNS [123,124].…”
Section: Hyperosmolar Bbb Disruptionmentioning
confidence: 87%
“…35,74,117 Additionally, recent research indicated that volume, not flow rate, of the mannitol injection is an important factor influencing the magnitude of the BBB disruption. 62 In addition to enhancing BBB permeability to drugs, use of mannitol in vivo has been shown to increase permeability of intraarterially injected viral vectors, 62,113 stem cells, 70 liposomal vehicles, 108 and antibodies such as BV. 23 In addition to opening the BBB, mannitol may decrease intratumoral hydrostatic pressure, which may enhance chemotherapy delivery by passive diffusion.…”
Section: Hyperosmotic Disruptionmentioning
confidence: 99%